A Cascade Multilevel Z-Source Inverter for Photovoltaic System - Thirumalini P; R. Arulmozhiyal; M Murali (Institute of Advanced Engineering and Science, 2015)
This paper describes a multilevel Z-source inverter for solar photovoltaic applications. The conventional power conversion topology performs either buck or boost the input voltage for non linear load depending upon duty ratio and modulation index in a multiple stage conversion with the help of impedance source passive network (L and C), which is usually known as Z-Source, which couples the n level source with input to the power source and increase the power efficiency. The multilevel z network capabilities of inverter are operated in the shoot through state of duty cycle and it acts as a filter to reduces the level of harmonics, stabilize power factor and to increase the output AC voltage range of inverter. To overcome further harmonics, multilevel level operation z source inverter compensates the fundamental level of harmonic in renewable. Proposed work as a whole involves the simulation part to design multilevel inverter. The output of the simulation is obtained by Simulink model using MATLAB.